Interactions between Cyanobacteria and Methane Processing Microbes Mitigate Methane Emissions from Rice Soils - Germán Pérez; Sascha M. B. Krause; Paul L. E. Bodelier; Marion Meima-Franke; Leonardo Pitombo; Pilar Irisarri (Microorganisms, 2023)
Cyanobacteria play a relevant role in rice soils due to their contribution to soil fertility through nitrogen (N2) fixation and as a promising strategy to mitigate methane (CH4) emissions from these systems. However, information is still limited regarding the mechanisms of cyanobacterial modulation of CH4 cycling in rice soils. Here, we focused on the response of methane cycling microbial communities to inoculation with cyanobacteria in rice soils. We performed a microcosm study comprising rice soil inoculated with either of two cyanobacterial isolates (Calothrix sp. and Nostoc sp.) obtained from a rice paddy. Our results demonstrate that cyanobacterial inoculation reduced CH4 emissions by 20 times. Yet, the effect on CH4 cycling microbes differed for the cyanobacterial strains. Type Ia methanotrophs were stimulated by Calothrix sp. in the surface layer, while Nostoc sp. had the opposite effect. The overall pmoA transcripts of Type Ib methanotrophs were stimulated by Nostoc. Methanogens were not affected in the surface layer, while their abundance was reduced in the sub surface layer by the presence of Nostoc sp. Our results indicate that mitigation of methane emission from rice soils based on cyanobacterial inoculants depends on the proper pairing of cyanobacteria–methanotrophs and their respective traits.